ANALISIS POLA STRUKTUR NARATIF SYD FIELD PADA FILM-FILM PENDEK INDONESIA PERAIH PENGHARGAAN INTERNASIONAL - Sherell Allycia Gievierna; Bernard Realino Danu Kristianto (KAGANGA KOMUNIKA: Journal of Communication Science, 2026)
Short films have increasingly emerged as a prominent audiovisual medium within the international festival ecosystem due to their ability to convey issues and creative expression through concise narratives. In recent years, several Indonesian short films have received awards at various global festivals, indicating that the strength of narrative structure is one of the key factors driving such recognition. This study aims to analyze the application of Syd Field’s three-act narrative structure in three Indonesian award-winning short films, namely Laut Memanggilku (2021), Evakuasi Mama Emola (2022), and Basri & Salma in a Never-ending Comedy (2023). The research employs a qualitative method with a textual analysis approach, applying the three-act structure to map the plot, conflict development, and narrative dynamics within each film. The findings reveal that all three films continue to exhibit the stages of the three-act structure, albeit with variations in development patterns, duration, and plot distribution. These results affirm that Syd Field’s three-act structure is adaptive and flexible within the context of Indonesian’s short films. The difference in these proportions demonstrates that each film employs a unique way of positioning its social issues within the narrative structure. This analysis provides insight into how narrative structure is constructed and adapted in Indonesian short films that have gained international recognition.   Keywords: Narrative Structure, Syd Field, Short Film, Three-Act Structure, Narrative Pattern, Social Issues